Spelling performance of public and private school students: A comparative study - Sampaio, Maria Nobre [UNESP]; Fusco, Natália [UNESP]; Romero, Ana Carla Leite [UNESP]; Amaral, Amanda Corrêa Do [UNESP]; Capellini, Simone Aparecida [UNESP] (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2017)
To characterize and compare the spelling performance of private and public students. Three hundred 1st-5th graders from public and private schools in the city of Marília, São Paulo, Brazil, were evaluated, totalizing 30 students from each grade, respectively. Collective and individual versions of the Pró-Ortografia test (a renowned Brazilian spelling test) were administered. There were significant inter-group differences indicating that private school students achieved higher performance. The mean values of correct answers of higher grade level students were statistically greater than those of the lower grade level students. The results indicated that the mean values of correct answers of all versions of the spelling test administered increased across grades for both private and public school students. However, the data evaluated showed that private school students attained higher spelling performance than public school students from the 2nd grade onwards.

O estudo buscou caracterizar e relacionar o desempenho ortográfico dos escolares de 1º ao 5º ano do ensino particular e público. Foram avaliados 300 escolares do 1º ao 5º ano em duas escolas, uma particular e outra pública, da cidade de Marília, São Paulo, sendo 30 alunos de cada ano escolar. Como procedimento, foi aplicado o Pró-Ortografia na sua versão coletiva e individual. Houve diferença estatisticamente significativa na comparação intergrupos, indicando desempenho superior dos escolares do ensino particular. Com o aumento da seriação, todos os grupos aumentaram a média de acertos nas provas avaliadas. Os resultados indicaram que as médias de acertos nas provas ortográficas se tornaram superiores com a progressão escolar tanto para os escolares do ensino particular quanto para os do ensino público. No entanto, os dados evidenciaram que os alunos do ensino particular apresentaram desempenho ortográfico superior em relação aos do ensino público a partir do 2º ano.
Desempenho ortográfico de escolares do ensino particular e público: estudo de caracterização e relação
Keywords: Evaluation; Handwriting; Learning; Teaching; Avaliação; Escrita manual; Aprendizagem; Ensino